Transformative Leadership: Empowering Human Capital in Senior High Schools - Samsur Samsur; Ahmad Rofi’i (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2024)
This research aims to analyze the leadership style of school principals in improving human resources, especially teacher performance, at SMA Negeri 1 Pacet Mojokerto. The school principal's leadership plays an important role in determining the success and quality of education in schools. An effective leadership style can increase motivation, teacher performance and student participation in the learning process. This research uses a descriptive method with a qualitative approach and a case study type. Data was collected through observation, interviews and documentation. The research results show that the leadership style applied by the school principal is democratic and participative. The principal considers teachers partners, builds teamwork, provides creative freedom, and accepts suggestions and criticism from subordinates. Efforts to improve human resources include providing opportunities to take part in training, upgrading educational seminars, coaching, and training in making lesson plans and syllabi, and implementing the independent curriculum. Obstacles include the lack of training programs outside of office hours and a lack of discipline for some teachers. However, adequate infrastructure and fairly frequent training are supporting factors. This research contributes to the development of educational management science, especially in principal leadership and improving human resources in schools. The research results can be a basis for formulating effective strategies and approaches to improve the quality of education in Indonesia.